SAFETY ASSESSMENT OF THE TANK WITH DIFFERENTIAL SETTLEMENT - LI ZhiHai; GAO HongLi; DENG FeiZhong (Jixie qiangdu)
Generally the settlement of spherical tank’s foundation is difficult to ensure complete uniformity. Especially the foundation has been used for years. There is always a certain differential settlement. Pillar stress of the tank will be uneven under differential settlement. The stress of a LPG spherical tank on use with multiple differential settlements is analyzed by elasticity model of finite element method. According to the analysis results under hydraulic testing pillar stress exceeds the yield strength of the material. Then elastoplastic model is established to analyze the impact of material nonlinearity of pillar. Through finite element analysis and experimental testing,whether the tank can be used is evaluated. Based on the analysis results the tank is recommended to use under low load and strong inspection.